2024
DOI: 10.1371/journal.pone.0298025
|View full text |Cite
|
Sign up to set email alerts
|

A DNA barcode library of Austrian geometridae (Lepidoptera) reveals high potential for DNA-based species identification

Benjamin Schattanek-Wiesmair,
Peter Huemer,
Christian Wieser
et al.

Abstract: Situated in the Eastern section of the European Alps, Austria encompasses a great diversity of different habitat types, ranging from alpine to lowland Pannonian ecosystems, and a correspondingly high level of species diversity, some of which has been addressed in various DNA barcoding projects. Here, we report a DNA barcode library of all the 476 species of Geometridae (Lepidoptera) that have been recorded in Austria. As far as possible, species were sampled from different Austrian regions in order to capture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…The conservative approach of the ASAP method seems congruent with our morphological investigation (Copilaş-Ciocianu et al, 2022), and the mPTP approach tended to oversplit (Song et al, 2018, Goulpeau et al, 2022). While the phenomenon of bin-sharing may arise here (e.g., Raupach et al, 2018; Raupach et al, 2020; Schattanek-Wiesmair et al, 2024), we can rule out this possibility since in some cases, the sequences are 100% identical for individuals classified morphologically as different types. This holds even when comparing Hungarian A. lotti individuals with German and Finnish A. uliginosus s.str.…”
Section: Discussionmentioning
confidence: 85%
“…The conservative approach of the ASAP method seems congruent with our morphological investigation (Copilaş-Ciocianu et al, 2022), and the mPTP approach tended to oversplit (Song et al, 2018, Goulpeau et al, 2022). While the phenomenon of bin-sharing may arise here (e.g., Raupach et al, 2018; Raupach et al, 2020; Schattanek-Wiesmair et al, 2024), we can rule out this possibility since in some cases, the sequences are 100% identical for individuals classified morphologically as different types. This holds even when comparing Hungarian A. lotti individuals with German and Finnish A. uliginosus s.str.…”
Section: Discussionmentioning
confidence: 85%
“… Hupało et al 2022 , Recuero and Caterino (2024b) ) or underestimating it (e.g. Ranasinghe et al (2023) , Schattanek-Wiesmair et al (2024) ), although studies on a diverse array of organisms has shown ASAP to be one of the most reliable single-locus species delimitation methods (e.g. Muster et al (2021) , Serrano and Ortiz (2023) , Solovyeva et al (2023) , Yin et al (2023) , Schattanek-Wiesmair et al (2024) ).…”
Section: Discussionmentioning
confidence: 99%
“… Ranasinghe et al (2023) , Schattanek-Wiesmair et al (2024) ), although studies on a diverse array of organisms has shown ASAP to be one of the most reliable single-locus species delimitation methods (e.g. Muster et al (2021) , Serrano and Ortiz (2023) , Solovyeva et al (2023) , Yin et al (2023) , Schattanek-Wiesmair et al (2024) ). With very few molecular studies on Diplura including different populations of the same species, there is little information on the typical intraspecific genetic distances in Diplura .…”
Section: Discussionmentioning
confidence: 99%